Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How does one find the following limits using the most basic limit properties (and also the limit definition for $ e $)?

a)$\lim_{x\rightarrow +\infty}\large{\frac{\sqrt[3]{x^2\sqrt{x^2+1}}+3x}{x}} $

b)$\lim_{x\rightarrow 0^+} \large{(2-e^{\arcsin^2\sqrt{x}})^{\frac{3}{x}}}$

c) $\lim_{x\rightarrow -\pi}\large{\frac {\sin(4x)}{x^2+\pi x}}$

Update: In the original version the limit in b) was with $x \to 0$. In this case since $\sqrt{x}$ is defined only for $x \geq 0$, the limit does not exist. So changed the limit to $x \to 0^+$.

share|cite|improve this question

For $(c)$ put $\displaystyle x+\pi=y\implies \sin4x=\sin 4(y-\pi)=\sin(4y-4\pi)=\sin4y$

$\displaystyle\lim_{x\rightarrow -\pi}\frac {\sin(4x)}{x^2+\pi x}=\lim_{y\to0}\frac{\sin 4y}{y(y-\pi)}$ Use $\lim_{u\to0}\frac{\sin u}u=1$

For $(a),$ $$\lim_{x\rightarrow +\infty}\frac{\sqrt[3]{x^2\sqrt{x^2+1}}+3x}x =\lim_{x\rightarrow +\infty}\frac{\sqrt[3]{\sqrt{x^6+x^4}}+3x}x=\lim_{x\rightarrow +\infty}\frac{(x^6+x^4)^{\frac16}+3x}x $$

Putting $\frac1x=h$, $$=\lim_{h\to0}(1+h^2)^{\frac16}+3=\cdots$$

share|cite|improve this answer

For $a$ (since $x>0$)$$\frac{\sqrt[3]{x^2\sqrt{x^2+1}}+3x}{x}=\frac{\sqrt[3]{x^2\sqrt{x^2+1}}}{\sqrt[3]{x^3}}+3=\sqrt[3]{x^{-1}\sqrt{x^2+1}}+3=\sqrt[3]{\sqrt{x^{-2}}\sqrt{x^2+1}}+3=\sqrt[3]{\sqrt{1+x^{-2}}}+3$$


share|cite|improve this answer
Thanks. Can you help me with b? – Constantine Oct 21 '13 at 17:21

I will try the limit in b) as other parts of the question have been solved quite nicely.

Let us write $L = \lim_{x \to 0}(2 - e^{\arcsin^{2}\sqrt{x}})^{3/x}$

Then we have

$\displaystyle \begin{aligned} \log L &= \log\left\{\lim_{x \to 0}(2 - e^{\arcsin^{2}\sqrt{x}})^{3/x}\right\} \\ &= \lim_{x \to 0}\log\left\{(2 - e^{\arcsin^{2}\sqrt{x}})^{3/x}\right\} \text{ (because of continuity of log) }\\ &= \lim_{x \to 0}\frac{3}{x}\log(2 - e^{\arcsin^{2}\sqrt{x}})\\ &= 3\lim_{x \to 0}\frac{\log(1 + 1 - e^{\arcsin^{2}\sqrt{x}})}{1 - e^{\arcsin^{2}\sqrt{x}}}\cdot\frac{1 - e^{\arcsin^{2}\sqrt{x}}}{x}\\ &= 3\lim_{x \to 0} 1\cdot \frac{1 - e^{\arcsin^{2}\sqrt{x}}}{x}\text{ (see explanation point 1 below) }\\ &= -3 \lim_{x \to 0} \frac{e^{\arcsin^{2}\sqrt{x}} - 1}{x}\\ &= -3\lim_{x \to 0} \frac{e^{\arcsin^{2}\sqrt{x}} - 1}{{\arcsin^{2}\sqrt{x}}}\cdot\frac{{\arcsin^{2}\sqrt{x}}}{x}\\ &= -3\lim_{x \to 0}1\cdot\left(\frac{\arcsin\sqrt{x}}{\sqrt{x}}\right)^{2}\text{ (see explanation point 2 below) }\\ &= -3\cdot 1^{2}\text{ (see explanation point 3 below) }\\ &= -3\end{aligned}$

Hence desired limit $L$ is given by $L = e^{-3}$.

Explanation for some steps: For calculating limits we can use following simple results:

1) $\displaystyle \lim_{y \to 0}\frac{\log(1 + y)}{y} = 1$

In the above problem we have $y = 1 - e^{\arcsin^{2}\sqrt{x}}$ so that $y \to 0$ as $x \to 0$ and hence the logarithmic limit evaluates to $1$.

2) $\displaystyle \lim_{y \to 0}\frac{e^{y} - 1}{y} = 1$

In this problem $y = \arcsin^{2}\sqrt{x}$ so that $y \to 0$ as $x \to 0$ and the exponential limit is also $1$.

3) $\displaystyle \lim_{y \to 0}\frac{\sin y}{y} = 1,\,\,\lim_{y \to 0}\frac{\arcsin y}{y} = 1$

Here $y = \sqrt{x}$ so that the arcsin limit evaluates to $1$.

In most common problems on limits these three fomulas suffice. When they don't (especially in some tough ones) I use L'Hospital Rule and if L'Hospital fails or generates complicated expression then only I opt for series expansions.

Update: The way question has been put the limit does not exist. We should change question so that $x \to 0+$.

share|cite|improve this answer

$$\lim_{x\to0}\left(2-e^{(\arcsin\sqrt x)^2}\right)^{\frac3x}$$

$$=\left(\lim_{x\to0}\left(1+1-e^{(\arcsin\sqrt x)^2}\right)^{\frac1{1-e^{(\arcsin\sqrt x)^2}}}\right)^{\lim_{x\to0}\frac{3(1-e^{(\arcsin\sqrt x)^2})}x}$$

For the inner limit put $\displaystyle1-e^{(\arcsin\sqrt x)^2}=\frac1n$ as $x\to0,n\to\infty\implies \lim_{n\to\infty}(1+\frac1n)^n=e$

For the limit in the power $$\lim_{x\to0}\frac{3(1-e^{(\arcsin\sqrt x)^2})}x=-3\lim_{x\to0}\frac{e^{(\arcsin\sqrt x)^2}-1}{(\arcsin\sqrt x)^2}\cdot \lim_{x\to0}\left(\frac{\arcsin\sqrt x}{\sqrt x}\right)^2$$

Put $(\arcsin\sqrt x)^2=h$ for the first limit and $\arcsin\sqrt x=u$ for the second to find $$\lim_{x\to0}\frac{3(1-e^{(\arcsin\sqrt x)^2})}x=-3$$

share|cite|improve this answer
@Constantine, I have answered $(b)$ separately for its complexity – lab bhattacharjee Oct 21 '13 at 18:44
The last step doesn't seem to help, you still have the indetermined $\frac {0}{0} $ form. – Constantine Oct 21 '13 at 19:04
@Constantine, have you noticed $$\lim_{x\to0}\frac{e^{(\arcsin\sqrt x)^2}-1}{(\arcsin\sqrt x)^2}=1$$ and $$\lim_{x\to0}\frac{\arcsin\sqrt x}{\sqrt x}=1$$ – lab bhattacharjee Oct 21 '13 at 19:06
I have noticed the second one, but the first one I don't understand. Where does it come from? – Constantine Oct 21 '13 at 19:14
@Constantine, are you talking about…? – lab bhattacharjee Oct 22 '13 at 4:28

Here is an approach. Notice that, when $x$ close to zero, then we have by Taylor series

$$ \arcsin^2\sqrt{x} \sim x. $$


$$ {(2-e^{\arcsin^2\sqrt{x}})^{\frac{3}{x}}}\sim {(2-e^{x})^{\frac{3}{x}}}=e^{\frac{3}{x}\ln(2-e^x)} = e^{\frac{3}{x}(-x+O(x^2))}\longrightarrow_{x\to 0} e^{-3} $$


$$ \ln(2-e^{x})=-x-x^2+O(x^3). $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.